Isochronous data link across a superconducting Nb flex cable with 5 femtojoules per bit. (1st April 2022) - Dai, Haitao; Kegerreis, Corey; Wehella Gamage, Deepal; Egan, Jonathan; Nielsen, Max; Chen, Yuan; Tuckerman, David; Peek, Sherman E; Yelamanchili, Bhargav; Hamilton, Michael; Das, Rabindra N; Herr, Anna; et al.
Abstract: Interconnect properties position superconducting digital circuits to build large, high performance, power efficient digital systems. We report a board-to-board communication data link, which is a critical technological component that has not yet been addressed. Synchronous communication on chip and between chips mounted on a common board is enabled by the superconducting resonant clock/power network for Reciprocal Quantum Logic circuits. The data link is extended to board-to-board communication using isochronous communication, where there is a common frequency between boards but the relative phase is unknown. Our link uses over-sampling and configurable delay at the receiver to synchronize to the local clock phase. A single-bit isochronous data link has been demonstrated on-chip through a transmission line, and on a multi-chip module through a superconducting tape between driver and receiver with variable phase offset. Measured results demonstrated correct functionality with a clock margin of 3 dB at 3.6 GHz, and with 5 fJ bit −1 at 4.2 K.